PENGARUH KUALITAS KEPEMIMPINAN DAN KEROHANIAN SEORANG PENDETA DALAM MENINGKATKAN KUALITAS KEROHANIAN, PELAYANAN DAN JUMLAH BAPTISAN DI GMAHK KOTA PALEMBANG - Milton T. Pardosi (Jurnal Koinonia, 2015)
The quality of leadership and spirituality of a pastor has a great influence inimproving the quality of spirituality and services of members which he is serving.When a pastor shows a good quality leadership and spirituality, then a member of thechurch will also grow in their spirituality and services. As a result, the church willgrow, especially in increasing the number of baptism. This is a formula that can notbe ignored by any pastor if he wants to achieve success in his ministry particularly inpromoting spirituality, ministry and number of baptism in his congregation.One of constraints faced today is the presence of pastors who haveproblems both in their quality of leadership and spirituality. This occurs because thepastors have not fully understand the significance of ministerial calling itself aswritten in Psalm 23: 1-6, Ezekiel 34: 1-30 and John 10: 1-15. When a pastor repeatsand realizes that he has received a ministerial calling in the beginning of his ministry,then it will help to increase his quality of leadership and spirituality.Therefore, a pastor demanded two things: commit to the ministerial calling(mission of a pastor, church and organization]); to give positive leadership andspiritual influences (to influence) to the members of the congregation in achievingthe goals of the church and organization. As a result, members of the congregationwill work together with the pastor in achieving the mission of the church of God inthis earth, discipleship (to Achieve).